Did Ignatius Know the Bishop of Rome? - Bernstein, C’Zar (The Evangelical quarterly, 2025)
Ignatius mentions no bishop of Rome in his letter to the Romans. Many scholars infer that there probably was no bishop of Rome for him to name. I shall argue that this inference from silence is unsafe. Ignatius mentions nobody at Rome, including presbyters and deacons—unlike his other letters. Rome’s lacking a bishop therefore cannot explain all the curious silence in Ign. Romans. Why the silence? I propose that a plausible explanation is protective anonymity: Ignatius sought to protect the Christians at Rome to whom he wrote. Finally, there are circumstantial signs in his letters that strongly suggest that he knew the bishop he did not name. If Ignatius wrote during Trajan’s reign, then monepiscopacy did not develop late at Rome. If Ignatius wrote well into the second century, as some scholars suppose, the counterpart for whose safety he was concerned may have been Hyginus or Pius.